Respiratory chain complex V deficiency due to a mutation in the assembly gene ATP12. Issue 2 (2nd February 2004) - De Meirleir, L; Seneca, S; Lissens, W; De Clercq, I; Eyskens, F; Gerlo, E; Smet, J; Van Coster, R
Abstract : In patients with mitochondrial encephalomyopathies an increasing number of causative gene defects have been detected. The number of identified pathogenic mitochondrial DNA mutations has largely increased over the past 15 years. Recently, much attention has turned to the investigation of nuclear oxidative phosphorylation (OXPHOS) gene defects. Within the OXPHOS defects, complex V deficiency is rarely found and, so far, these defects have only been attributed to mutations in the mitochondrial MTATP6 gene. Mutation analysis of the complete coding regions at the cDNA level of the nuclear ATP11, ATP12, ATPα, ATPβ and ATPγ genes and the mitochondrial MTATP6 and MTAT8 genes was undertaken in two unrelated patients. Blue Native polyacrylamide gel electrophoresis followed by catalytic staining had already documented their complex V decreased activity. Extensive molecular analysis of five nuclear and two mitochondrial genes revealed a mutation in the ATP12 assembly gene in one patient. This mutation is believed to be the cause of the impaired complex V activity. To our knowledge, this is the first report of a pathogenic mutation in a human nuclear encoded ATPase assembly gene.